Traditional Knowledge of Tharu Community on Plants Used For 'Marcha' (Fermented Cake) Preparation in Benimanipur Vdc Of NawalparasiDistrict, Western Nepal. - Thapa, Kantiprabha; Rajbhandary, Sangeeta (Journal of Natural History Museum, 2009)
Nepal is rich in ethnobotanical information and there are many plants of ethnobotanical values used by various ethnic community and many studies have been carried out in this aspect. The present study was carried out on the western part of Nepal, in Benimanipur VDC, Nawalparasi district focusing mainly on the plants used in 'Marcha' preparation. Data were collected from two field visits from May-June and September 2006. A total of 20 plant species were found as 'Marcha' preparing plants in Tharu community, which were collected and preserved. The traditional technique of 'Marcha' preparation along with different species of plants used by the Tharu community was documented. The different sample of 'Marcha' with different combination of plants was also documented. This paper does highlight the commonly used plants for 'Marcha' preparation by Tharu community. Keywords: Asparagus racemosus; Elephantopus scaber; Piper longum; Fermentation starter; Beverages. Journal of Natural History Museum Vol. 24, 2009 Page: 137-145